Congenital Bleeding Disorders and COVID-19—A Systematic Literature Review - Dorgalaleh, Akbar; Safdari, Seyed Mehrab; Tabibian, Shadi; Shams, Mahmood; Dabbagh, Ali; Rezazadeh, Azadeh (Seminars in Thrombosis and Hemostasis, 2023)
Hypercoagulability is a prominent feature of coronavirus disease 2019 (COVID-19) and can lead to fatal consequences. Although the impact of COVID-19 on several disorders is well-established, its effect on congenital bleeding disorders (CBDs) is not well-documented. To address this ambiguity, a systematic review was conducted on the available studies to determine the impact of COVID-19 and vaccination aimed to prevent COVID-19 on patients with CBDs. We performed a systematic literature review using relevant keywords and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) protocol. We conducted our search on the PubMed, Scopus, and Web of Science databases until July 2023. Out of 31 included studies, 12 case series covering 770 patients with CBD and COVID-19 were further analyzed. The majority of the patients had hemophilia A (n = 352, ∼46%) or hemophilia B (n = 74, ∼10%), while the remaining patients had von Willebrand disease (n = 43, 5.6%) or rare bleeding disorders (n = 27, 3.5%). A total of 25 deaths (3.2%) and 22 intensive care unit admissions (2.8%) were recorded. Bleeding complications were reported in the majority of the 12 case series (n = 7, 58.3%) and in most of the case reports (n = 8, ∼57%), while thrombotic complications were only reported in two studies (16.6%). The mortality rate ranged from 0% in five studies (41.6%) to 5.7% and the rate of hospitalization ranged from 0 to 40%. Bleeding complications were reported in a range of 0 to 81%, while the thrombotic complication rate in one study was 6.9%. The mortality rate varied from 0 to 5.7%, and the hospitalization rate ranged from 0 to 40%. Bleeding complications were reported in a range of 0 to 81%, while the rate of thrombotic complications in one study was 6.9%. Vaccination was reported in five case series, which included 821 patients with CBDs with the majority having hemophilia A (n = 479; 67.2%) and hemophilia B (n = 85; ∼12%). The most frequently reported side effects were myalgia (6.5%), flu-like symptoms (4.8%), fever (4.7%), and headache (4%). COVID-19 in patients with CBDs appears to provoke thrombotic complications and bleeding events more frequently, as well as a higher rate of hospitalization, which may be partially due to the increased risk of bleeding events. Although it seems that patients with CBD have lower mortality rates, further studies are necessary to fully understand this, especially considering comorbidities and low number of available studies.
Keywords: congenital bleeding disorders; COVID-19; SARS-CoV-2; thrombosis; bleeding; mortality